Participatory action research as a strategy for empowering Aboriginal health workers - Rosalind Hecker (Elsevier, 1997)
Abstract: A participatory action research project was undertaken with Aboriginal health workerson the Anangu Pitjantjatjara Lands in South Australia. The study examined the factors that affect the empowerment of Aboriginal health workers within the context of an Aboriginal-controlled primary health care service. This project was different from previous research conducted with Aboriginal healdi workers in remote areas for two reasons. First, it enabled them to participate actively as co-researchers in the study, and second, it brought about action and change during the research process. The three main factors preventing Aboriginal health workers from attaining a key role within the health service are the standard of training they receive, their low literacy and numeracy levels, and their lack of participation in decision making within the health service. Each of these factors is interrelated and all affect the Aboriginal healdi workers' ability to have more control and responsibility within the health service.